LAPAROSCOPIC APPROACH TO A RARE INTERSTITIAL INCISIONAL HERNIA FOLLOWING APPENDECTOMY - Ulucay, Kerim Erdem; Younis, Muhammad Umar (Journal of Ayub Medical College Abbottabad, 2017)
Among the complications of an open appendectomy is the presentation of an incisional hernia. An interstitial or interparietal hernia is the one in which the hernia sac is present between the muscle layers of the abdominal wall which makes the presentation of a post-operative incisional interstitial hernia quite a rarity. A 52-year-old female was admitted through the outpatient clinic presenting with the complaints of discomfort and a bulge felt in the right hypochondrium for the last 3 years. Radiological investigations were able to delineate an interstitial incisional hernia through the previous open appendectomy scar. A laparoscopic approach to repair of this hernia was successfully undertaken without any complications. This is an interesting case of incisional hernia that may pose a diagnostic challenge to the unsuspecting surgeon with an unusual presentation which may cause unnecessary delays in treatment as well as unnecessary operations. Very few comparable cases can be found in literature. Keywords: interstitial hernia; open appendectomy; Incisional hernia; Laparoscopy